2010
DOI: 10.2174/187152910790780087
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Targeting of Endothelial Progenitor Cells

Abstract: The endothelium entered the field of regenerative medicine with the discovery of endothelial progenitor cells (EPCs). These cells participate in endothelial homeostasis and are actively involved in physiological and pathological neovascularization. Despite the unresolved discussion about the very phenotype of these cells, great efforts have been devoted to study the role of EPCs in cardiovascular diseases. EPCs are very rare in peripheral circulation and are further reduced in association with cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 191 publications
(250 reference statements)
1
7
0
Order By: Relevance
“…Thus, it appears that both lysates do not affect EPCs functional activities in a dose dependent manner, while the largest effects of LJ on viability and adhesion capacity occur at the lowest concentrations ( Figures 1 – 3 , panels A). A double-edged or biphasic action on EPCs with no or detrimental effects at higher-doses has been reported for several compounds including statins, thiazolidinediones and even insulin [44] , [56] . Also resveratrol, at low doses promotes antioxidant effects while at higher doses can have a dose-dependent pro-oxidant role followed by cell damage and apoptosis [57] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, it appears that both lysates do not affect EPCs functional activities in a dose dependent manner, while the largest effects of LJ on viability and adhesion capacity occur at the lowest concentrations ( Figures 1 – 3 , panels A). A double-edged or biphasic action on EPCs with no or detrimental effects at higher-doses has been reported for several compounds including statins, thiazolidinediones and even insulin [44] , [56] . Also resveratrol, at low doses promotes antioxidant effects while at higher doses can have a dose-dependent pro-oxidant role followed by cell damage and apoptosis [57] .…”
Section: Discussionmentioning
confidence: 96%
“…Recently EPCs number and function have become the target of pharmaceutical compounds such as statins, renin-angiotensin system blockers, and some classes of glucose-lowering agents (thiazolidinediones and dipeptidyl peptidase-4 inhibitors) [44] , [45] ; furthermore, several natural anti-oxidative compounds with anti-inflammatory properties have also been found to enhance EPCs bioactivity, even if large clinical trials testing the effects of antioxidants on cardiovascular risk resulted in systematic failures [46] , [47] . These disappointing results are probably related to the limited effects of traditional antioxidants on intracellular ROS production, while they exert a scavenging action on already formed ROS [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Circulating bone marrow derived cells, defined as early endothelial progenitor cells (EPCs), can proliferate multiple times and differentiate into endothelial cells [3031]. Recent studies have shown that mobilization and differentiation of EPCs play an important role in augmenting neovascularization and endothelial replacement in the ischemic and injured heart [3234].…”
Section: Discussionmentioning
confidence: 99%
“…Once in the bloodstream, EPC specifically home to sites of vascular damage through chemokine sensing, e.g. via the CXCR4/SDF-1a or the RANTES / CCR5 axis, the IL-8 / GRO-CXC system interacting with CXCR2, as well as 2-integrins and Eselectin [56]. After adhesion to the local endothelial layer, EPCs either act as a cell patch to repair endothelial discontinuity or migrate through the interstitium and participate in the formation of new blood vessels.…”
Section: Estrogens Serms and Endothelial Progenitor Cellsmentioning
confidence: 99%
“…As a result, even in the presence of a normal ischemic mobilization, EPCs would be unable to repair a damaged tissue. For all these reasons, ways to stimulate EPC-mediated cardiovascular repair are actively pursued [56]. Iwakura et al first documented that estrogens are essential for the ability of EPCs to repair an experimental arterial injury.…”
Section: Estrogens Serms and Endothelial Progenitor Cellsmentioning
confidence: 99%